Students’ Writing Error in Parts of Speech: A Case Study of EFL Students - Meikardo Samuel Prayuda; Juliana Juliana; Nova Florentina Ambarwati; Fiber Yun Almanda Ginting; Candra Ronitua Gultom (Jurnal Educatio FKIP UNMA, 2023)
This research was intended to see the phenomena of students capability in producing products of their language target which was English. This was purposed to observe and to find their errors in producing writings. The result then could be used as reflection to improve their skill in writing specifically in parts of speech. From the analysis, it was found out that the errors found in the students writing were dominated by noun with the percentage of 22%, followed by pronoun 19%, adjective 17%, verb 14%, conjunction 14%, adverb 8%, preposition 6%, and lastly interjection 0.2 %. The data then analysed by considering the analysis in error analysis and found out that 33% error in misordering, 23% error in omission, 22% error in misformation, and 22% error in addition. This research showed that error which appear the most was dominated by misordering error and noun in the aspect of parts of speech. The possible cause of how the errors could happened was because of the influence of intralingual transfer. Students cannot differentiate between their experience in using grammar of source language and target language. Thus, the product of target language that provided by the students met errors.